2018
DOI: 10.1038/s41598-018-33180-w
|View full text |Cite
|
Sign up to set email alerts
|

Temporal differentiation of bovine airway epithelial cells grown at an air-liquid interface

Abstract: There is an urgent need to develop improved, physiologically-relevant in vitro models of airway epithelia with which to better understand the pathological processes associated with infection, allergies and toxicological insults of the respiratory tract of both humans and domesticated animals. In the present study, we have characterised the proliferation and differentiation of primary bovine bronchial epithelial cells (BBECs) grown at an air-liquid interface (ALI) at three-day intervals over a period of 42 days… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 92 publications
1
32
0
Order By: Relevance
“…Another study also showed that the TEER of human nasal epithelial cells cultured in a LLI system dropped to approximately 500 Ω.cm 2 after reaching the maximum TEER value (3,133 ± 665 Ω.cm 2)45 . The drop in TEER values before stabilization could be related to the beginning of cell senescence 46 or differentiation state of the cells 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study also showed that the TEER of human nasal epithelial cells cultured in a LLI system dropped to approximately 500 Ω.cm 2 after reaching the maximum TEER value (3,133 ± 665 Ω.cm 2)45 . The drop in TEER values before stabilization could be related to the beginning of cell senescence 46 or differentiation state of the cells 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The model forms a heavily ciliated, mucus-producing cell layer with similar physiology to that of the native respiratory tissue. In tandem, we have developed a BBEC culture model which well represents the respiratory epithelium of cattle 26,27 . The sero-specific nature of severe cases of respiratory disease by M. haemolytica 11,38 , coupled with a suggested role for the polysaccharide capsule (on which the serotyping classification is based) in cell adhesion 17 , indicates that isolates may be specifically adapted to colonising the airway tissues of discrete hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine bronchial epithelial cells can be stimulated to differentiate into a more representative model of the in vivo microenvironment through exposure to the atmosphere [36, 37, 59]. The methodology for differentiation of bovine airway epithelial cells have been fully optimised [44] and the model well-characterised [45]. The differentiated BBEC model has been shown to replicate the hallmark defences of the respiratory tract, including active mucocilary clearance.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously investigated the growth conditions required for optimal growth and differentiation of bovine bronchial epithelial cells at an ALI [44] and assessed the temporal differentiation of these cells to identify an optimum window suitable for infection studies [45]. The aim of the present study was to investigate the interactions of a panel of M. haemolytica isolates, representing virulent and commensal strains recovered from both cattle and sheep, with differentiated bovine bronchial epithelial cells grown at an ALI.…”
Section: Introductionmentioning
confidence: 99%